APLIKASI KAMUS BAHASA SASAK HALUS MENGGUNAKAN ANDROID - Muh. Fahrurrozi; Lalu Puji Indra Kharisma; Khairunnazri (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2020)
Sasak Language is one of the regional languages used to communicate by the people of Lombok, West Nusa Tenggara. But along with the development of technology, especially in the field of Android smartphones, the Sasak language has begun to fade, not a few people in Lombok who do not understand the language, Lombok Sasak vocabulary especially the current generation. This is caused by environmental factors of family, school and friends who use Indonesian in daily conversation. The solution to this problem is to design an Android-based Sasak Smooth dictionary application. The main purpose of the Sasak Halus dictionary application is to assist them in finding Indonesian or Sasak Halus translations effectively and efficiently on smartphone media. Sasak Fine-language dictionary application based on Android-based APPS in the form of an installer that can be used on Android-based smartphones with a minimum version of 4.00 and above. In testing using black box testing and testing on smartphones, the application can run smoothly.